2014
DOI: 10.1016/j.cplett.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced coupled twisted intramolecular charge transfer and excited-state proton transfer via intermolecular hydrogen bonding: A DFT/TD-DFT study

Abstract: coupled twisted intramolecular charge transfer and excited-state proton transfer via intermolecular hydrogen bonding: a DFT/TD-DFT study, Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…1,11,12 Numerous experimental and theoretical investigations, including time-resolved spectroscopic methods 6,13–17 and time-dependent density functional theory (TDDFT) and molecular dynamics simulations, 18–25 have been focused on the ICT in the excited state. The structural changes of chromophores such as the internal rotation of the electron donor or acceptor group have often been proposed by theoretical investigations, 18–22,26–30 but such structural changes accompanying the ICT have rarely been implemented experimentally. 15,31–35…”
Section: Introductionmentioning
confidence: 99%
“…1,11,12 Numerous experimental and theoretical investigations, including time-resolved spectroscopic methods 6,13–17 and time-dependent density functional theory (TDDFT) and molecular dynamics simulations, 18–25 have been focused on the ICT in the excited state. The structural changes of chromophores such as the internal rotation of the electron donor or acceptor group have often been proposed by theoretical investigations, 18–22,26–30 but such structural changes accompanying the ICT have rarely been implemented experimentally. 15,31–35…”
Section: Introductionmentioning
confidence: 99%
“…The DFT/TDDFT methods are suitable to study the mechanism involving PT, ESIPT, and ICT process. For instance, by using these calculation methods, our group has successfully proposed the mechanism for thiazolidinedione derivative in dimethylformamide solution that TICT could facilitate ESIPT initiated by intermolecular hydrogen-bond strengthening in the S 1 state . Zhao’s group clearly demonstrated that for N,N -dimethylanilino-1,3-diketone (DMADK) chromophore, the ESIPT and TICT process were coupled in the S 1 state rather than sequential ESIPT and TICT process, and these calculated results are consistent with those reported by Ciofini’s group …”
Section: Introductionmentioning
confidence: 99%